2017
DOI: 10.1111/imb.12300
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations and expression changes of acetyl‐coenzyme A carboxylase are associated with spirotetramat resistance in Aphis gossypii Glover

Abstract: Acetyl-coenzyme A carboxylase (ACC) catalyses the carboxylation of acetyl-coenzyme A (acetyl-CoA) to produce malonyl-CoA during the de novo synthesis of fatty acids. Spirotetramat, an inhibitor of ACC, is widely used to control a range of sucking insects, including the Aphis gossypii. In the present study, Reverse transcription quantitative real-time PCR (RT-qPCR) results demonstrated that ACC was significantly overexpressed in a laboratory-selected spirotetramat-resistant strain compared with the susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To control this pest in such crops, several insecticides have been developed and adopted into Integrated Pest Management (IPM) packages worldwide 30 33 . However, the use of insecticides has some drawbacks, which are known for their potential side effects on non-target organisms 34 , such as aphid natural enemies 35 , 36 , and for the development of insecticide resistance in aphids 37 , 38 . Therefore, non-chemical control strategies, such as biological control 39 – 41 , biopesticides 42 , 43 , and plant resistance should be prioritized for the sustainable control of aphid pests.…”
Section: Introductionmentioning
confidence: 99%
“…To control this pest in such crops, several insecticides have been developed and adopted into Integrated Pest Management (IPM) packages worldwide 30 33 . However, the use of insecticides has some drawbacks, which are known for their potential side effects on non-target organisms 34 , such as aphid natural enemies 35 , 36 , and for the development of insecticide resistance in aphids 37 , 38 . Therefore, non-chemical control strategies, such as biological control 39 – 41 , biopesticides 42 , 43 , and plant resistance should be prioritized for the sustainable control of aphid pests.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known of the molecular basis of this resistance. 46,49,50 Mechanisms of resistance to insecticides are associated with ACC gene mutations [60][61][62] or enhanced detoxification, such as P450 genes 49,50 or uridine diphosphate-glycosyltransferases (UDP-UGTs). 63 For example, our previous work showed that high expression of the P450 genes CYP380C6, CYP4CJ1, CYP6DA2, CYP6CY7 and CYP6CY21 is involved in resistance to cyantraniliprole in A. gossypii.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi and CRISPR/Cas9 can then be used to validate the functional roles of alleles hypothesised to be involved in resistance (Pan et al . 2017; Wang et al . 2017; Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomics and genome-wide associations can be used to correlate molecular variation and resistance phenotypes (Bass et al 2013;Tay et al 2015;Walsh et al 2018;Wybouw et al 2019). RNAi and CRISPR/Cas9 can then be used to validate the functional roles of alleles hypothesised to be involved in resistance (Pan et al 2017;Wang et al 2017;Wang et al 2018;Guest et al 2019). A priori candidate genes can be incorporated into genomic pipelines, but a large benefit of genomic approaches is that they provide scope to assess the role of genes without pre-existing expectations of their contribution to resistance.…”
Section: Discussionmentioning
confidence: 99%